Antimicrobial activity of bacteriocins of lactic acid bacteria on Listeria monocytogenes, Staphylococcus aureus and Clostridium tyrobutyricum in cheese production - Dolenčić Špehar, Iva (Array, 2020)
The generally accepted concept of the necessity of producing safe foods has indirectly influenced the decision to replace chemical preservatives with natural ones. Bacteriocins, and in particular those synthesized by lactic acid bacteria (LAB) in the food industry, are considered to be their effective replacement. In controlling the growth of microbial pathogens and/or the occurrence of pathogenic bacteria in food, with the permitted nisin and pediocin, a significant antibacterial effect has been shown for most LAB bacteriocins. However, the use of purified bacteriocins as bio preservatives in cheese production is limited. To inhibit the growth of bacteria L. monocytogenes, S. aureus and C. tyrobutyricum in cheese, bacteriocinogenic LAB strains contained in primary, adjunct or protective culture are much more acceptable in cheese production.